Echocardiographic features in antiphospholipid-negative Sneddon's syndrome and potential association with severity of neurological symptoms or recurrence of strokes: a longitudinal cohort study. (3rd January 2020) - Assan, Florence; de Zuttere, Dominique; Bottin, Laure; Tavolaro, Sebastian; Courvoisier, Delphine S; Barbaud, Annick; Alamowitch, Sonia; Francès, Camille; Chasset, François
Abstract: Aims: Sneddon's syndrome (SS) may be classified as antiphospholipid positive (aPL + ) or negative (aPL − SS). An association between Libman–Sacks (LS) endocarditis and strokes has been described in aPL + patients. To describe cardiac involvement in aPL − SS and assess the potential association between LS endocarditis and severity or recurrence of neurological symptoms. Methods and results: This longitudinal cohort study included aPL − SS patients followed in our departments between 1991 and June 2018. All patients underwent transthoracic 2D and Doppler echocardiography at diagnosis. Follow-up echocardiography was performed annually and the potential relationship between LS endocarditis development and neurovascular relapse as well as long-term cardiac worsening was prospectively assessed. We included 61 patients [52 women; median age 45 (range 24–60)]. For valvular involvement, 36 (59%) patients showed leaflet thickening; 18 (29.5%) had LS endocarditis at baseline. During a median follow-up of 72 months, LS endocarditis developed in eight (17.4%) patients, and 13 (28.3%) showed significant worsening of their cardiac status, including two who needed valvular replacement. After adjusting for baseline antithrombotic treatment regimen, neither the presence of LS endocarditis at baseline nor development during follow-up was associated with neurological relapse [hazard ratio (HR): 1.06, 95% confidence interval (CI): 0.33–4.74, P = 0.92] and [HR: 0.38, 95% CI: 0.02–1.89, P = 0.31], respectively. Conclusion: A long-term follow-up is needed to detect cardiac complications in aPL − SS. No change in neurological relapse was observed in patients presenting LS endocarditis occurrence during follow-up without any modification in antithrombotic treatment. Further research is necessary to assess the usefulness of treatment escalation in these patients.